Transparansi Atau Manipulasi? Menggali Praktik Manajemen Laba dalam Laporan Keuangan Perusahaan - Diah Lestari , R. A. Widyanti (Universitas Batam, 2025)
This research aims to explore the factors influencing earnings management practices and their implications for the quality of financial reporting and corporate reputation. Using a Systematic Literature Review (SLR) methodology, the study synthesizes findings from various existing studies on earnings management, agency theory, and signaling theory. The results indicate that earnings management can improve short-term financial outcomes but has long-term consequences on credibility and trustworthiness, which may undermine investor confidence. The study concludes with recommendations for companies to balance stakeholder expectations with the need to maintain transparent and reliable financial reporting systems to ensure long-term sustainability and corporate integrity.